Effectiveness Of Lavender Aromatherapy On Perineal Pain Intensity In Post Partum Women : Evidence Based Case Report - Khoerani, Fikriya; Widiawati, Ida; Resmana, Rika (Jurnal Kesehatan Siliwangi, 2024)
Background: Perineal pain is physiological for mothers who have just given birth, but this pain interferes with their ability to move, which can cause complications such as postpartum bleeding. One non-pharmacological method that can be used is lavender aromatherapy to reduce the perineal pain you feel. Aromatherapy stimulates the hypothalamus, or pituitary gland, to release endorphins, which cause feelings of calm, serenity, and happiness. In addition, the active ingredients lavender, linaool and linalyl acetate, function as an analgesic. Purpose:The aim of this case study is to apply lavender aromatherapy to reduce perineal pain in post partum mothers. Method: The method used is searching for evidence through databases from PubMed and Google Scholar with publication years 2019 – 2023, full text, experimental research design/systematic review, in English or Indonesian. Results: The results of the case report show that lavender aromatherapy reduces perineal pain in post partum mothers who experience perineal wound pain, before being given the intervention they get a pain score of 6 and after being given the intervention for 1 hour they get a pain score of 3. Conclusion: lavender aromatherapy reduces perineal pain in mothers postpartum.